2002
DOI: 10.1007/s00268-001-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism: Renal calcium excretion in patients with and without renal stone disease before and after parathyroidectomy

Abstract: The effect of parathyroidectomy on renal calcium excretion per 24 hours in patients with primary hyperparathyroidism with and without a history of renal stone disease was evaluated. Altogether, 91 patients operated on for primary hyperparathyroidism formed the study group for preoperative analysis. Of these patients, 42 were evaluated 1 to 3 years postoperatively. The median preoperative serum calcium level was 2.92 mmol/L, and it was the same for patients with or without renal stones. Preoperatively we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Overall, renal calcium excretion is reduced after PTX (18,37,38). However, in some (14,18) but not all (37) studies, an increased 24-h U-Ca has been found after PTX in patients with a history of nephrolithiasis.…”
Section: Effects Of Ptx On 24-h U-ca and Risk Of Nephrolithiasismentioning
confidence: 91%
See 3 more Smart Citations
“…Overall, renal calcium excretion is reduced after PTX (18,37,38). However, in some (14,18) but not all (37) studies, an increased 24-h U-Ca has been found after PTX in patients with a history of nephrolithiasis.…”
Section: Effects Of Ptx On 24-h U-ca and Risk Of Nephrolithiasismentioning
confidence: 91%
“…However, in some (14,18) but not all (37) studies, an increased 24-h U-Ca has been found after PTX in patients with a history of nephrolithiasis. In a cohort of 42 patients who had successful PTX, reevaluation of 24-h U-Ca 1-3 yr after surgery showed a higher 24-h U-Ca in the group with renal stone disease compared with the patients without a history of renal stones (18).…”
Section: Effects Of Ptx On 24-h U-ca and Risk Of Nephrolithiasismentioning
confidence: 93%
See 2 more Smart Citations
“…Combining these findings with the increased risk of fracture during daily life in men (8)(9)(10)(11), it may be necessary to review the current differences in the BMD T-score levels between men and women. The renal function is prone to compromise in patients with PHPT due to hypercalcemia and the presence of urinary tract stones, and an eGFR of <60 mL/min/1.73 m 2 (equivalent to CKD stage III) is one of the criterion included in the guidelines for PHPT management (12)(13)(14). In the present study, the mean eGFR was 79.9±26.7 mL/min (men: 74.9±24.9, women: 81.6±27.3), and the number of patients with an eGFR of <60 mL/min was only 17 (six men and 11 women).…”
Section: Discussionmentioning
confidence: 99%